Acute Paraparesis Due to Protrusion of a Disc Following Lateral Interbody Fusion for Degenerative Kyphoscoliosis: A Case Report. Issue 1 (January 2019) - Ruchirawan, Surawut; Fujita, Nobuyuki; Yagi, Mitsuru; Tsuji, Osahiko; Okada, Eijiro; Nagoshi, Narihito; Ishii, Ken; Nakamura, Masaya; Matsumoto, Morio; Watanabe, Kota
Abstract : Case: A 74-year-old woman presented with severe trunk deformity. Radiographs revealed severe sagittal and coronal imbalance with spinal canal stenosis at L4 to L5. Anterior cages were placed at L2 to L3, L3 to L4, and L4 to L5. Three days later, posterior correction surgery from T5 to the ilium with decompression at L4 to L5 was performed. At 30 minutes after surgery, leg muscle strength severely deteriorated. Emergency surgery revealed disc fragments protruding into the spinal canal at L2 to L3. Conclusion: Because posteriorly placed extreme lateral interbody fusion (XLIF) cages can be a risk factor for disc protrusion into the spinal canal, computed tomographic evaluation or prophylactic posterior decompression should be considered before the correction procedure.